Contribuições de encontros de diálogo ao longo do pré-natal - Corrêa, Carla Regina de Almeida (Universidade Federal de São Carlos, 2016)
The gestation period is known as a time full of great transformations, such as physical, hormonal or emotional ones. In this period, most women experience some anxiety about themselves and the baby care, making it a space favorable to achieve and/or modify knowledge about it. This study had as object “A meeting for some dialogue and its repercussion to maternity”; and, based on this, it proposes to understand the influence of these dialogues during the prenatal in the parentally process, paying attention to the use of a social network. The theoretical reference adopted is George-Hans Gadamer‟s Hermeneutics and the methodological reference is the Thematic Content Analysis.Data were collected by a semi-structured questionnaire, obtaining a deep and complete narrative based on the starting question “Tell me about the opportunity to talk during the prenatal. What was your perception?” Participated of the study seven women who went to the meetings more than three times and accepted to take part of it. The meetings for some dialogue occurred from October, 2014 to August, 2015, in the countryside of a city in the state of Sao Paulo, Brazil; data were collected in a period between forty-five and sixty days after the childbirth. Data analysis showed two themes: “Informational Support” and “Emotional Support and Acknowledgment of Themselves”It was identified that the participation inthese meetings for some dialogue during the prenatal was important for women who built a dialogic movement in the acknowledgment of themselves and the others as an emotional and informational social support. These dialogues emancipate the pregnant mothers to take decisions on how to take care of their children, promote a social network increase and contribute for the acceptanceof the support received.Besides, these meetings permitted that these women, individually, developed the process of parentally building, recognizing themselves as mothers and creating opportunities for the fathers approaching in this auto recognizing movement.
Keywords: Gestação; Parentalidade; Apoio social; Cuidado pré-natal; Cuidado pós-parto; Gestation; Parentally; Social support; Prenatal care; Postpartum care; CIENCIAS DA SAUDE::ENFERMAGEM